Postcolonial Identities and Visual Art Education – A Case Study of Sri Lanka - Udagedara, P. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
Visual art education in Sri Lanka has historically, theoretically, and comparatively been investigated in a postcolonial context. Through examination of historical situations, this study focuses on how visual art education has been and continues to be marginalized, ignored, and only utilized to achieve a dominant national ideology or to propagate the political agendas of various forces and actors. The study also raises questions about the bureaucratic national cultural superiority observed in culturally embodied pedagogies adopted in art education and examine the ways in which such pedagogies sideline innovativeness, ethnic diversity, and the socio-cultural contexts in which art education happens. This research challenges the institutional and national recognition accorded to visual art as a social unifier or cleanser. Focusing on this issue, the study attempts to reframe the history of visual art teaching seeking to identify impediments and shortcomings in the past and present with a broader context. The study proposes recommendations based on innovativeness that would be necessary for drafting a national visual art education policy which would gravitate towards a national creative economy. This, in turn, would provide an opportunity to examine the legacy and current position of Sri Lankan visual art education from multiple positions and perspectives.
Keywords: Visual art education; Postcolonial identities; Institutional structure; Pedagogy; Creative wulture